Conversion of Conventional Bank to Sharia Bank: Conversion Analysis of Academic Conversions: Cases in Province Nanggroe Aceh Darussalam and Lombok NTB - Lukman Hakim; Dwi Novita; Dewi Rahmawati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Bank is a business entity that collects funds from the public in the form of savings and distributes them to the public in the form of credit or other forms. In Indonesia, there are many banks both in the form of conventional and Islamic banks, the more rapid the development of digital banks, the significant changes are now also visible, one of which is that there are several areas such as in Nangroe Aceh Darussalam and Lombok West Nusa Tenggara (NTB) which convert from conventional banks to Islamic banks. Bank NTB Syari'ah is proven to be in 8th place and contributes 2% to the market share of Islamic banks. The total population of NTB in 2020 reached 5,320,092. The total population of Aceh in 2020 reached 5,274,871. The two provinces have approximately the same population, then the Islamic community is both very strong, the ecosystem supports, especially in NTB halal tourism is growing rapidly. The conversion system carried out is investigated for further discussion, How is Conventional Bank Conversion to Sharia Bank? How is the Analysis of Conversion of Contracts Against Conventional Banks to Sharia Banks?. This research is very useful to see how the conversion of Conventional Banks to Sharia Banks has been implemented, this research can be a reference and constructive input as well as a reference in the context of the implementation of Sharia Bank Conversion in Indonesia. The basis used by banks in transferring or converting existing non-syari'ah transaction products into sharia transactions is by referring to DSN Fatwa No. 31/DSN-MUI/IV/2002 concerning Debt Transfer. Keywords: Bank Conversion, Aceh, Lombok, Conventional Banks, Islamic Bank.